Labour Exploitation, Gender Violence and Barriers to Reproductive and Sexual Rights - Letizia Palumbo (Sociologia del Diritto)
In recent years, significant research has explored, from both a sociological and legal perspective, the structural nature of labour exploitation and its connections to gender-based violence, with a particular focus on migrant women workers. In line with this perspective, this article examines the interplay between labour exploitation, gender-based violence – including domestic violence – and access to the right to health, particularly sexual and reproductive health. It focuses on the experiences of migrant women employed in the agricultural sector in rural Italy, discussing key theoretical and legal issues related to the concepts of labour exploitation, gender-based violence and reproductive justice. The article sheds light on the pervasive nature of exploitation that extends far beyond the experience of work in the strict sense, deeply permeating many aspects of the living conditions – thus also the health – of women workers, when intertwined with patriarchal practices and oppressions, as well as various situations of intersectional vulnerability.